(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the specific features of ethological relations and behavioral reactions in the aphid population, ethological structure, as well as the variety of formation of the aphid colony were explained; The main manifestations of behavioral reactions in aphids, that is, aphid feeding and habitat selection, swarm diversity, formation and re-formation, aphid protection, aphid relationships with other insects, aphid egg-laying and reproduction, adaptability of aphids to changing environmental conditions were explained;